2010
DOI: 10.1007/s00436-010-1961-4
|View full text |Cite
|
Sign up to set email alerts
|

A human case of subcutaneous dirofilariasis caused by Dirofilaria repens in Vietnam: histologic and molecular confirmation

Abstract: Human dirofilariasis caused by infection with Dirofilaria worms has been frequently reported. The symptoms associated with infection by these filarial parasites, which are transmitted to humans by zooanthropophilic mosquitoes, are characterized by mainly pulmonary and subcutaneous nodules. Here, we report the first case in Vietnam of a subcutaneous dirofilariasis with a painful nodule in the right eyelid. An immature female worm was removed by excisional biopsy and identified as Dirofilaria repens by histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The occurrence of multiple nodules also suggests that the dog is a suitable host, in contrast to humans (aberrant host), in whom single subcutaneous masses are detected. 34,35 In addition, the simultaneous presence of adult worms and immature stages confirms that live adults were present, unlike the situation in humans, in whom adult worms are usually not sexually mature. [34][35][36] Whether the nodules caused by D. repens are caused by direct mechanical action by the nematodes or due to chronic inflammation remains to be explored.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The occurrence of multiple nodules also suggests that the dog is a suitable host, in contrast to humans (aberrant host), in whom single subcutaneous masses are detected. 34,35 In addition, the simultaneous presence of adult worms and immature stages confirms that live adults were present, unlike the situation in humans, in whom adult worms are usually not sexually mature. [34][35][36] Whether the nodules caused by D. repens are caused by direct mechanical action by the nematodes or due to chronic inflammation remains to be explored.…”
Section: Discussionmentioning
confidence: 93%
“…34,35 In addition, the simultaneous presence of adult worms and immature stages confirms that live adults were present, unlike the situation in humans, in whom adult worms are usually not sexually mature. [34][35][36] Whether the nodules caused by D. repens are caused by direct mechanical action by the nematodes or due to chronic inflammation remains to be explored. 34 Histological studies on human hosts affected by subcutaneous dirofilariosis demonstrated that living onchocercids may elicit the production of growth factor b, a cytokine playing a critical role in the homeostasis of an organism, which induces a mixed response linked to immunosuppression and neo-angiogenesis, thus contributing to the survival of the parasite.…”
Section: Discussionmentioning
confidence: 93%
“…We chose the cox1 gene for genetic characterization of the Dirofilaria isolates in our study because this gene can reliably differentiate between different species of filariae, and it has also been used for the identification of Dirofilaria in previous studies (7,9,12,20,22,30). The reported mean nucleotide distance of the cox1 gene within species ranges from 0% to 2% (9), and there is less than 1% difference between available D. repens sequences in the GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, the filarial worm of this species was first reported from a human conjunctiva in 2008 [12], and another was reported from the human subcutaneous tissue in 2010 [13]. This is the 3rd report of human D. repens infection in Vietnam which involved the conjunctiva or subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%